Efficacy and safety of PCSK9 inhibitors, potent statins, and their combinations for reducing low-density lipoprotein cholesterol in hyperlipidemia patients: a systematic network meta-analysis - Jiang, Yuhua; Wang, Yingying; Ma, Sijia; Qian, Linlin; Jing, Yeteng; Chen, Xi; Yang, Jinsheng (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe objective of this study is to assess the relative efficacy of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors, such as alirocumab, evolocumab, and inclisiran, in conjunction with potent statins like atorvastatin and rosuvastatin, in patients presenting with hyperlipidemia or heightened cardiovascular risk attributable to elevated low-density lipoprotein cholesterol (LDL-C).MethodsA systematic search was conducted across databases including PubMed, Embase, and the Cochrane Library to explore lipid-lowering therapies in hyperlipidemia from their inception to 7 November 2023. A network meta-analysis (NMA) was conducted via Stata 17 software, with two authors independently conducting the search, screening, and data abstraction.ResultsA total of 68 clinical studies involving 21,288 patients with hyperlipidemia were incorporated into the NMA. PSCK9 inhibitors and potent statins significantly reduced LDL-C levels from baseline vs. placebo regardless of background therapy. Regarding the efficacy of lipid reduction, four principal medications were evaluated: evolocumab and atorvastatin [mean standard deviation (MD) −3.41, 95% CI −4.81 to −2.00] and evolocumab with rosuvastatin (MD −3.44, 95% CI −5.10 to −1.78) vs. placebo; alirocumab combined with rosuvastatin (MD −2.91, 95% CI −3.95 to −1.88) and alirocumab with atorvastatin (MD −2.90, 95% CI −3.97 to −1.84) vs. placebo. Meanwhile, compared with placebo, evolocumab (MD −1.89, 95% CI −2.27 to −1.50), alirocumab (MD −1.83, 95% CI −2.09 to −1.57), rosuvastatin (MD −1.93, 95% CI −2.30 to −1.56), inclisiran (MD −1.68, 95% CI −2.10 to −1.27), and atorvastatin (MD −1.68, 95% CI −2.04 to −1.31) could also play a role in the treatment of LDL-C reduction. Moreover, the incidence of adverse events (AEs) was similar to that observed in the control group, which included both placebo and potent statin groups, with no significant differences identified in our study (P > 0.05).ConclusionsThe combination of PCSK9 inhibitors with robust statins like rosuvastatin and atorvastatin markedly decreases LDL-C levels in patients with hyperlipidemia when compared to placebo or monotherapy. Notably, the pairing of evolocumab and atorvastatin exhibited exceptional efficacy in this investigation. In the interim, the combination of PCSK9 inhibitors and potent statins demonstrates a notable safety profile when contrasted with the control group.